Modeling mechanical properties of a shear thickening fluid damper based on phase transition theory. (26th April 2018) - Wei, Minghai; Lin, Kun; Guo, Qian
Abstract: Shear thickening fluids (STFs) are highly concentrated colloidal suspensions consisting of monodisperse nano-particles suspended in a carrying fluid, and have the capacity to display both flowable and rigid behaviors, when subjected to sudden stimuli. In that process, the external energy that acts on an STF can be dissipated quickly. The aim of this study is to present a dynamic model of a damper filled with STF that can be directly used in control engineering fields. To this end, shear stress during phase transition of the STF material is chosen as an internal variable. A non-convex function with bifurcation behavior is used to describe the phase transitioning of STF by determining the relationship between the behavioral characteristics of the microscopic phase and macroscopic damping force. This model is able to predict force-velocity and force-displacement relationships as functions of the loading frequency. Efficacy of the model is demonstrated via comparison with experimental results from previous studies. In addition, the results confirm the hypothesis regarding the occurrence of STF phase transitioning when subject to shear stress.